Pendampingan Pembuatan Iklan Layanan Masyarakat Di SMKN 1 Kopang - Renda, Rapi (Institut Agama Islam Hamzanwadi NW Pancor, 2024)
Assistance in making public service advertisements at the SMA/SMK and equivalent level aims to educate the community around Kopang sub-district, Central Lombok district. The methods used are classical and practical, strengthening the theory of visual communication design. This assistance was carried out first by lobbying the school so that this activity could be carried out for four days; After organizing the event, it was presented to the school. This assistance was permitted by the school. Mentoring activities start Monday 26-29 February 2024; In this activity, assistance was carried out by inviting local teachers to collaborate in assisting students in creating community service advertisements (PSAs). Students are provided with classical material and tips and tricks in designing. Next, the students tried to make designs with the themes of the dangers of drugs, early marriage and caring for the environment. Of these three themes, students choose one to work on. The work process is accompanied by local lecturers and teachers to get good results. After going through the design stage which was carried out for three days and on the fourth day the students were taught and accompanied to learn to print on A3 size paper. The implication of this assistance is that the school directs the graphic design material taught at school more, it is beneficial for everyone, especially the school environment, and the results can be displayed in each class.